Sustainable Tourism Observatories Framework at National Tourism Strategic Area Development (KSPN) in Indonesia - Muhamad, Muhamad; Baiquni, Muhammad; Wiryanto, Wiryanto (Universitas Prasetiya Mulya, 2024)
This study aims to establish a framework that integrates planning and implementation programs for sustainable tourism development in Indonesia, providing a guide for stakeholders to unify understanding and drive policy agreements. The framework emphasizes concise, transparent, measurable, and adjustable principles for monitoring Sustainable Tourism Development (STD) guidelines. Using methodologies including surveys, case studies, comparative studies, time and motion analysis, and documentation analysis, this research identifies key elements and characteristics of sustainable tourism phenomena. The findings highlight the critical role of stakeholders in monitoring sustainable tourism through periodic reporting processes led by the Sustainable Tourism Observatory (STO). Government bodies, academic institutions, and community stakeholders collaboratively develop sustainable travel destinations, fostering accelerated tourism growth and sustainability in Indonesia.